2022
DOI: 10.3389/fonc.2022.943423
|View full text |Cite
|
Sign up to set email alerts
|

High preoperative white blood cell count determines poor prognosis and is associated with an immunosuppressive microenvironment in colorectal cancer

Abstract: BackgroundThe correlation between high white blood cell (WBC) count and poor prognosis has been identified in various types of cancer; however, the clinical significance and immune context of WBC count in colorectal cancer remains unclear.MethodsBetween February 2009 and November 2014, 7,433 patients at the Shanghai Cancer Center who had undergone elective surgery for colorectal cancer were enrolled in this retrospective cohort study. Patients were divided into two groups: low and high preoperative WBC groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The multivariable Cox regression analysis showed that a higher WBC count and monocyte counts were significantly correlated with an increased risk of disability and mortality among patients with HD. Elevated total WBC count and monocyte count have been reported to be a significant indicator of reduced survival in patients with cardiovascular disease ( 52 ) and cancer ( 53 ), showing a positive correlation with all-cause mortality ( 54 ). This is the first study to demonstrate an association between higher WBC count and monocyte and HD prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The multivariable Cox regression analysis showed that a higher WBC count and monocyte counts were significantly correlated with an increased risk of disability and mortality among patients with HD. Elevated total WBC count and monocyte count have been reported to be a significant indicator of reduced survival in patients with cardiovascular disease ( 52 ) and cancer ( 53 ), showing a positive correlation with all-cause mortality ( 54 ). This is the first study to demonstrate an association between higher WBC count and monocyte and HD prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that WBCs, an inflammatory factor, play a crucial role in the development, growth, infiltration, and spread of tumors. As a result, WBC counts in patients with advanced NSCLC have been shown to have predictive value for prognosis when undergoing immunotherapy [ 27 , 28 ]. Moreover, most studies have consistently demonstrated that baseline WBC count exhibits a greater predictive capacity [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The white blood cell (WBC) count is an important laboratory parameter that reflects the body’s immune response and inflammatory status. In the context of thyroid nodules, alterations in WBC count have been investigated as a potential marker for distinguishing between benign and malignant thyroid cancer [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%